Drug resistance among students with pulmonary tuberculosis: a study based on screening in Henan, China - Jiying Xu; Yanqiu Zhang; Guojie Wang; Jianguo Jiang; Wenqiong Du; Saige Chen; Dan Meng; Wenshuai Suo; Yan Zhuang; Kan Wang; Weidong Wang; Dongyang Zhao (BMC Infectious Diseases)
Abstract Background Tuberculosis (TB) can easily spread among students and can lead to an outbreak once there is an infection in a school. Outbreaks of drug-resistant TB (DR-TB) in schools have occasionally been reported, but the profile of DR-TB in students in a province has rarely been described. This study was conducted to determine the prevalence of DR-TB and factors associated with it in students in Henan Province, China. Methods We retrospectively reviewed the data of 3527 pulmonary TB patients among students with culture-confirmed Mycobacterium tuberculosis (M.tb) isolates collected from the Tuberculosis Information Management System of the China Disease Prevention and Control Information System from 2015 to 2021. Prevalence of DR-TB was analyzed. Comparisons between categorical variables were analyzed using the chi-square test or Fisher’s exact test as appropriate. Logistic regression models were used to identify the factors associated with DR-TB. Results Any DR-, RR (rifampin resistance)- and MDR (multi-drug resistance) -TB rates in students were 10.46%, 7.91% and 6.10%, respectively. And they all showed a downward trend from 2015 to 2021 (p < 0.001). Previously treated cases were 7.30 (95% CI: 5.30, 10.05), 8.60 (95% CI: 6.14,12.14) and 9.43 (95% CI: 6.64,13.40) times more likely than the new cases to be diagnosed with Any DR-TB, RR-TB and MDR-TB, respectively. Patients from schools in the western region of Henan had greater odds of having Any DR- (AOR = 2.06, 95% CI: 1.31, 3.24), RR- (AOR = 2.81, 95% CI: 1.66, 4.76) and MDR-TB (AOR = 2.07, 95% CI: 1.13, 3.80) than those from schools in the northern region. Males had a 1.40-fold (95% CI: 1.11, 1.78), 1.34-fold (95% CI: 1.02, 1.75) greater likelihood of being diagnosed with Any DR- and RR-TB, respectively. The risk of being diagnosed with MDR-TB was 1.42 (95% CI: 1.00, 2.02) times greater in students migrant between prefectures of the province than in the locals. Conclusion The prevalence of DR-TB among students with PTB in Henan, China, significantly decreased from 2015 to 2021. Previous treated cases and those in west-region schools in Henan were at greater risk of being diagnosed with Any DR-, RR- and MDR-TB. In addition, males were more likely to be diagnosed with Any DR- and RR-TB. It requires further study that whether those who migrated between prefectures of the province were more likely to be diagnosed with MDR-TB.